A137 TISSUE-TRANSGLUTAMINASE ANTIBODY HIGHER THAN 10 TIMES THE NORMAL VALUE IS A RELIABLE PREDICTIVE TEST OF VILLOUS ATROPHY IN PATIENTS WITH SUSPICION OF CELIAC DISEASE. (15th March 2019) - Nguyen, T; Portolese, O V; Patey, N; Dal Soglio, D; Oligny, L; Dirks, M; Jantchou, P
Abstract: Background: Tissue-transglutaminase antibody (tTGA) is a dependable test for patients with suspicion of celiac disease (CD). Since 2012, the European Society of Pediatric Gastroenterology Hepatology and Nutrition (ESPGHAN) has suggested that the diagnostic of CD could be established if tTGA levels are greater than 10 times the normal value (10N). Nonetheless, this has not been adopted in North America where endoscopies with biopsies still remain the gold standard for CD diagnosis. Several studies have been conducted in Europe to validate the ESPGHAN guidelines but none in children in Canada. Aims: To assess the reliability of the tTGA cut-off value of 10 times the normal level for the diagnosis of CD. Hence, the primary aim was to analyse the performance of the tTGA test in patients with suspicion of CD. The secondary aim was to assess whether a different cut-off value (25N) would perform better. Methods: Baseline tTGA levels and histological results were collected and analysed in a prospective cohort of children with a suspicion of CD seen at the gastroenterology unit of Sainte-Justine Hospital between 2011 and 2018. The tTGA kit used in the study was INOVA Diagnostics' kit Quanta Lite (R) h-tTG IgA ELISA. The histological results of duodenal biopsies were considered as indicative of CD if the Marsh classification was ≥2. With a cut-off tTGA value of 40 UI/mL (10N), we calculated the positive predictive value (PPV), the specificity and the receiver operating curve (ROC) curve. In addition, analyses were performed for a cut-off value of 100 UI/mL (25N). All analyses were carried out with SAS Statistical Software 9.4. Results: 272 patients were included in the study. The median age (Interquartile range(IQR)) at diagnosis was 8.9 (5.60, 12.05) years. CD was confirmed by biopsy in 234 cases. The tTGA level was higher than 10N in 155 (56.99%) children and more than 25N in 121 (44.49%) children. Using a tTGA cut-off of 40 UI/mL, the PPV was 99.35% (95% CI: 96.46%-99.98%), the specificity was 97.37% (95% CI : 86.19%-99.93%) and the area under curve (AUC) was 0.933. For a tTGA level >100 UI/mL, the PPV and specificity were respectively 99.17% (95% CI: 95.48%-99.98%) and 97.37% (95% CI : 86.19%-99.93%). Only 1 child in the study had a false positive: a 2-year old with tTGA >100 UI/mL and a normal biopsy. However, the tTGA control performed the day of the biopsy turned out normal. Conclusions: This study validates the reliability of the tTGA test when using a cut-off level of 10 and 25 times the normal value since specificity and PPV results were high. These findings suggest that in children with suspicion of CD half of the endoscopies could be avoided. Therefore, a change in the diagnostic approach of CD in children could be implemented in Quebec. Funding Agencies: None